IMPLEMENTASI PERATURAN MENTERI PENDAYAGUNAAN APARATUR NEGARA DAN REFORMASI BIROKRASI NOMOR 1 TAHUN 2020 DI BADAN KEPEGAWAIAN DAERAH KOTA PASURUAN - Amelya, Adelyta Rizky (Jurnal Administrasi Publik, 2024)
One of the roles of apparatus resource management is how to get the right people, both quality, as well as the number and place in accordance with the abilities, education and expertise, skills and experience needed in the organization in supporting the smooth running of the main tasks and functions of the organization. Apparatus resource management applied by the government is in the arrangement of regional staffing. But in reality, the condition of regional staffing, especially in the Pasuruan City Government, is still in low quality and there are still apparatus placed in certain positions that are not appropriate. Therefore, the Minister of State Apparatus and Bureaucratic Reform Regulation Number 1 of 2020 concerning Position Analysis Guidelines was issued. However, at the level of implementation, a number of problems arise, including policy standards and policy assessments that are not yet directed, understanding of the content and content of policies that are still low, low communication and coordination between implementing organizations, the availability of human resources in carrying out policies that need to be improved and the commitment of implementers or implementors in carrying out the content of policies that are still far from the expectations and objectives of the initial policy setting, so that the implementation of the policy is still in line with the expectations and objectives of the policy.